(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: People with pre-diabetes, if not detected and managed in time, will turn to diabetes. Dyslipidemia in people with diabetes increases the risk of death from cardiovascular disease. Therefore, early detection of dyslipidemia in pre-diabetic patients for timely intervention and treatment helps to slow down the progression of the disease and prevention of serious complications caused by co-morbidities, reducing treatment costs, and increasing quality of life for patients are necessary. Objectives: Determine the prevalence of dyslipidemia and learn some related factors in pre-diabetic patients who come for health examination at C hospital in Da Nang. Materials and Methods: This is a descriptive cross-sectional study on 242 patients, who came for health examination at Da Nang C Hospital from November 2022 to May 2023. They were identified as pre-diabetes, recorded information related to the patient’s age, gender, occupation, and blood pressure, BMI, smoking and family history of diabetes through the information collection form, fasting blood glucose, HbA1c, Total Cholesterol, Triglyceride, HDL-c tests. Collected data were handled by the medical statistical method with the support of Stata 14.0 software. Results: The rate of dyslipidemia is 83.06%; nondyslipidemia was 16.94%. Disorders of TC, TG and LDL-c account for a high percentage (60.74%, 52.89% and 52.89%). Disorders of 2 lipid components accounted for 36.36%, disorders of 4 blood lipid components accounted for 2.48%. There is a relationship between dyslipidemia and hypertension and family history of diabetes (p ≤ 0.05). There was no association between dyslipidemia with age, gender and occupation, BMI, smoking (p > 0.05). Conclusion: The prevalence of dyslipidemia in pre-diabetes patients is 83.06%; in which the rate of disorders of TC, TG and LDL-c is 60.74%, respectively; 52.89% and 52.89%. Disorders of 2 lipid components accounted for the highest rate of 36.36%, proving that prediabetes is a high risk factor leading to dyslipidemia.